RASIONAL-KONSTRUKTIVIS: INDONESIA DI PERSIMPANGAN JALAN MERESPON KEBIJAKAN ‘TURN BACK THE BOATS’ AUSTRALIA - Maajid, Ahmad Luthfi; Susitianingsih, Hermini; Rosyidin, Mohammad (Journal of International Relations, 2016)
The flow of asylum seekers caused by the many conflicts that arose in theMiddle East and around Asia since about 2001 led Australia to start behavingantipathy to them. Those asylum seekers usually called boat people. Then, itbecomes a reason for Australia to apply restrictive asylum policies. One of thepolicy is called 'turn back the boats' namely by bringing back the boat peoplewho indicated from Indonesia back to Indonesia. This causes asylum seekersexploded in Indonesia region and impacted negative causes. Indonesia wasforced to accept these asylum seekers even though it is detrimental and was notan obligation for Indonesia. This paper intends to analyze the dilemma ofIndonesia to address the Australian policy and asylum-seekers issue usingrationalist and constructivist theory. On the one hand, Indonesia in accordancewith the rationalist view, refuse the asylums and Australia’s policy because ofthe cost-benefit considerations and it is not the obligation for Indonesia.However, on the other hand, Indonesia recessive condition forced to accept theboat people and it is consistent with the constructivist view. But apparently,constructivist still has not succeeded explaining this somehow-unique caseconsidering that Indonesia has no commitment in conducting the reception ofthe asylum seekers.